The Impact of Laser Irradiation on Thin ZrN Films Deposited by Pulsed DC Magnetron Sputtering - Ameena Nazneen; Penghui Lei; Di Yun (Nanomaterials)
Transition metal nitrides have extensive applications, including magnetic storage devices, hardware resistance coatings, and low-temperature fuel cells. This study investigated the structural, electrical, and mechanical properties of thin zirconium nitride (ZrN) films by examining the effects of laser irradiation times. Thin ZrN films were deposited on glass substrates using pulsed DC magnetron sputtering and irradiated with a diode laser for 6 and 10 min. Characterization was performed using X-ray diffraction (XRD), scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HRTEM), nanoindentation, and four-point probe techniques. Extended laser irradiation times resulted in increased numbers of peaks on XRD analysis, indicating enhanced crystalline behavior of thin ZrN film. SEM analysis revealed surface voids, while HRTEM showed nanostructured ZrN with uniform plane orientation. The electrical properties of the thin ZrN film improved with extended laser irradiation, as demonstrated by a reduction in sheet resistance from 0.43 × 109 Ω to 0.04 × 109 Ω. Additionally, nanoindentation tests revealed an increase in hardness, rising from 8.91 GPa to 9.36 GPa.